Incongruence of subjective memory impairment ratings and the experience of memory problems in older adults without dementia: a mixed methods study. (3rd August 2018) - Hill, Nikki; Mogle, Jacqueline; Kitko, Lisa; Gilmore-Bykovskyi, Andrea; Wion, Rachel; Kitt-Lewis, Erin; Kolanowski, Ann
ABSTRACT: Objectives: The objective of this study was to describe the experiences of older adults living with subjective memory impairment (SMI) and examine the extent to which SMI severity was associated with impact of SMI on daily life. Method: A mixed methods convergent design was utilized. Participants with SMI ( n = 19, mean age 80.7 years) were recruited from community settings. Semi-structured interviews were analyzed using thematic analysis; these findings were integrated with descriptive statistics from questionnaire and cognitive status data. Results: The impact of SMI varied depending on the personal meaning individuals attributed to the experience. Older adults with normal cognition reported episodic memory problem compared to more pervasive problems reported by participants with mild cognitive deficits. The impact of memory problems ranged from frustration/embarrassment to avoidance of social activities, but the degree of emotional impact was not reflected in SMI severity or cognitive status. Conclusion: SMI is common in older adults without dementia but the impact on function and well-being is variable and does not seem to be associated with objective cognition. Future research is needed to validate these associations and to inform the development of SMI measures that accurately reflect older adults' experiences.